CSIG-10. PHARMACO-PHOSPHO-PROTEO-GENOMICS OF PEDIATRIC HIGH-GRADE GLIOMAS – A PILOT STUDY. (14th November 2022) - Findlay, Izac; Staudt, Dilana; Kearney, Padraic; McEwen, Holly; Duchatel, Ryan; Jackson, Evangeline; Beitaki, Tyrone; Smith, Nathan; Vitanza, Nicholas; Firestein, Ron; Cain, Jason; Mueller, Sabine; et al.
Abstract: Pediatric high-grade gliomas (pHGG) are the leading cause of cancer-related death in children and young adults. Current treatment strategies are centered on maximal safe resection, followed by radiotherapy, and interrogation of the tumor genome to identify targetable mutations. Unfortunately, we are yet to see an improvement in patient outcomes with a median overall survival remaining 15-months. To improve patient outcomes, we have begun to characterize the genome, proteome, and phosphoproteome of 168 pHGGs to better understand the functional consequences of their somatic alterations as well as their influence of the tumor microenvironment. Employing a novel 'pharmaco-phospho-proteo-genomics' pipeline, we have analyzed pHGG cell lines and tumor tissue specimens at diagnosis, relapse (partial resection congenital glioblastoma), and autopsy. Genomic profiling was conducted utilizing the 523-gene TruSight Oncology 500 (TSO500) next-generation sequencing panel. Simultaneously, tumor proteomes and phosphoproteomes were characterized using our high-throughput global phospho-proteomic profiling technique termed pHASED (phospho Heavy-labelled-spiketide FAIMS StEpped-CV DDA). High-fidelity tumor proteomic and phospho-proteomic data were identified and compared to normal control brain samples. Across 40 pHGG samples, we identified 290 unique somatic alterations with a high predicted impact severity and quantified 7, 345 unique proteins and 3, 327 phosphoproteins. Gene panel sequencing of a critical pediatric glioblastoma patient sample identified 18 somatic alterations, eight of which had a high predicted impact severity, however, none were targetable. Conversely, phosphoproteomic profiling identified enriched MAPK and PRKCB signaling, relative to normal brain tissues, thereby encouraging the use of the TGA/FDA approved therapies trametinib (MAPKs) and enzastaurin (PRKCB). In vitro investigations confirmed the utility of these treatment approaches and in vivo patient derives xenograft mouse models for this sample are under investigation. This pilot study provides critical data to support the benefit of interrogating the genome, proteome, and phospho-proteome of these devastating tumours to aid in the selection/development of effective treatment strategies.